Detection of Hedyotis corymbosa (L.) Lam. in traditional Chinese medicine Hedyotis diffusa Willd. with the Proofman-LMTIA method - Yongzhen Wang; Juan Tian; Dan Zhou; Deguo Wang; Bailing Yin (Pharmacia, 2025)
There is increasing demand for the traditional Chinese medicine Hedyotis diffusa Willd. due to its effectiveness in treating hepatitis and malignant tumors of the liver, lung, and stomach. Hedyotis corymbosa (L.) Lam. has commonly become an adulterant of H. diffusa Willd. The proofreading enzyme-mediated probe cleavage coupled with ladder-shape melting temperature isothermal amplification (Proofman-LMTIA) can specifically and sensitively detect nucleic acids. In this study, the Proofman-LMTIA method was established to identify H. corymbosa (L.) Lam. for quality control of the traditional Chinese medicine Hedyotis diffusa Willd. The LMTIA primers and Proofman probe were designed using the internal transcribed spacer 2 (ITS2) of H. corymbosa (L.) Lam. as the target. The reaction temperature was optimized, and the specificity and sensitivity were determined. The repeatability and reliability were also assessed. The optimal reaction temperature of the Proofman-LMTIA method was 61 °C. The method demonstrated high specificity, repeatability, reliability, and sensitivity, with amplification completed within 20 min and a detection limit of 10 pg/μL genomic H. corymbosa (L.) Lam. This study successfully established a Proofman-LMTIA method for the detection of H. corymbosa (L.) Lam., providing an effective approach to distinguish authentic from adulterated traditional Chinese medicine.